Effect of Al doping on optical properties of ZnO thin films: theory and experiment - Kovalenko, M.; Bovgyra, O.; Dzikovskyi, V.; Kashuba, A.; Ilchuk, H.; Petrus, R.; Semkiv, I. (Physics and Chemistry of Solid State, 2021)
The structural, electronic, and optical properties of zinc oxide thin films with Al-doping have been investigated experimentally and with density functional theory (DFT) calculations. Changes in properties of doped thin films, which are deposited on a glass substrate by a high-frequency magnetron sputtering method, are monitored using X-ray diffraction data and UV measurements. Our theoretical calculations show that the electronic structure of ZnO: Al can be well described by the DFT+U method. The XRD measurements demonstrated the formation of a pure single ZnO phase and Al atoms is well incorporated in the ZnO lattice. Also, we determine the optical constants such as optical dielectric function, refractive index, optical band gap values, extinction coefficient, and optical conductivity of the doping films through transmittance spectra. The calculated results show the change of lattice parameters Al-doped ZnO. The optical band gap of ZnO: Al is increased compared with pure ZnO. Besides, around the Fermi level of Al-doped ZnO was emerged the shallow donor states from mainly 3s-Al states. Our DFT calculations of optical properties Al-doped ZnO agree satisfactorily with the experimentally measured transmittance values.